Development and Implementation of a “Virtual Team Coordination Application” for Enhanced Remote Work Efficiency - Rajan; Sukhmanpreet Singh Virk; Loveleen Kaur; Dr. Rajbir Kaur (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2024)
With the contemporary increasingly computerized and distanced workplace, effective group coordination is fundamental for maintaining coherence, productivity, and cooperation. The Virtual Group Coordination Application aims to ease communication, task management, and cooperation between staff using Microsoft PowerApps. This application acts as a central platform in which the clients can design and track errands, monitor progress, and cooperate through open dialogue, thereby dealing with common problems remote teams face. The application comes with some of the powerful features found in PowerApps, delivering a native UI, through which employees are able to navigate through several functionalities, including a task and deadline track as well as the exchange of documents. In addition, it integrates tools to update as well as alerts to ensure that tasks are completed timely, which then fosters accountability and better overall crew performance. The application also highlights information security and client jobs to ensure that all sensitive information is only accessible by an authorized work force. Applying the security job idea of PowerApps, the application ensures that its group information remains intact as it provides a customized adjustable experience tailored to the specific needs of various associations. In general, the Virtual Group Coordination Application is a comprehensive solution designed to promote virtual cooperation, collaborate in the best ways possible, and support productivity in an offsite work environment.